Effect of a school‐based oral health education programme on use of recommended oral self‐care for reducing the risk of caries by children in Nigeria. Issue 4 (21st November 2014) - Esan, Ayodeji; Folayan, Morenike Oluwatoyin; Egbetade, Grace O; Oyedele, Titus Ayodeji
<x xml:space="preserve">Abstract</x> Objective Caries is a major oral health problem children with efforts focused on promoting use of caries prevention methods. The aim of the study is to assess the effect of a school‐based oral health education programme on use of oral self‐care measures for reducing caries. Methods A structured school‐based oral health education programme was implemented in six schools in Ile‐Ife, Nigeria for 4 years. At the end of the project, information was sought from school children in their last year and final 2 years of studies on the use of fluoridated toothpaste, consumption of sugar‐containing snacks more than once a day, frequency of tooth brushing and flossing, and time of the last dental check‐up. Predictors of the use of preventive oral health practices for caries were determined. Results School children who received the intervention were more likely to report frequent use of fluoride‐containing toothpastes (P < 0.001), more likely to brush twice a day (P = 0.03), less likely to consuming sugar‐containing snacks less than once a day (P = 0.03) and less likely to use dental floss once a day (P < 0.001) when compared to the control group. Conclusion This long term school based educational programme was able to increase school children's use of fluoride‐containing toothpaste and twice daily tooth brushing, which are critical tools for reducing the risk of caries.